The Regulatory Commitment Problem, Industry Structures and Investment Incentives in Network Quality Upgrades - Dkhil, Ines Ben; Jebsi, Khaireddine; Baranes, Edmond (Asian Journal of Economic Modelling, 2022)
This paper examines how the timing of access price regulation and the incumbent firm’s structure affect the investment incentives relating to network upgrades. We consider a general setting with non-ad-hoc specifications for the service quality and investment fixed cost functions, and we compare different possible scenarios for vertically integrated industry structures and the timing of regulatory actions. First, we show that the competition-investment trade-off may be solved when the regulator can fix the access price before the integrated network provider’s investment decision. Second, we show that the sole requirement of vertical separation on the incumbent firm is no guarantee for the viability of service-based competition, since foreclosure cannot be avoided in the absence of access price regulation. Third, we show that monopoly is socially preferable to retail competition when the investment spillover is high, and the regulator cannot commit ex-ante to the access price.